Hadith #2851 - Sunan Abi Dawud - Abu Idrees al-Khulani أبو إدريس الخولاني; Abu Tha'laba al-Khushni; Bsr bin 'Ubaidullah بسر بن عبيد الله الحضرمي; Da'ud bin 'Amr bin Zuhayr داود بن عمرو الضبي; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان (Sunan Abi Dawud)
The Prophet (ﷺ) said: Eat what ever is caught for you by a dog or a hawk you have trained and set off when you have mentioned Allah’s name. I said: (Does this apply) if it killed (the animal)? He said: When it kills it without eating any of it, for it caught it only for you. Abu Dawud said: If a hawk eats any of it, there is no harm (in eating it). If a dog eats it, it is disapproved (to eat the meat). If it drinks blood, there is no harm (in eating it).
Grade: Da'if

Hadith #4946 - Sunan Abi Dawud - Abu al-Darda; Amr bin 'Awn/'Auf bin Aws; Da'ud bin 'Amr bin Zuhayr داود بن عمرو الضبي; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
If anyone removes his brother’s anxiety of this world, Allah will remove for him one of the anxieties of the Day of resurrection; if anyone makes easy for an impoverished man, Allah will make easy for him in this world and on the day of resurrection; if anyone conceals a Muslim’s secrets, Allah will conceal his secrets in this world and on the Day of resurrection; Allah will remain in the aid of a servant so long as the servant remains in the aid of his brother. Abu Dawud said: ‘Uthman did
Grade: Sahih